(untitled) (Bangladesh Journal of Medical Microbiology, 2011)
Bacteriological quality of treated water of different sources was determined by presumptive coliform count. In source-wise distribution of samples, 50% of mineral water, 87.5% of filtered water and 100% of tap water samples were exceeded the drinking water guideline value of WHO. Microorganisms in tap water comprised Escherichia coli spp. (60%), Klebsiella spp. (40%), Enterobacter spp. (20%), Pseudomonas spp. (70%), Proteus spp. (10%), Staphylococcus spp. (40%) and Salmonella spp. (0%). Furthermore, there was no correlation between faecal coliform and the presence of Salmonella species. Results obtained from this investigation revealed that municipal tap water of Dhaka city was contaminated with a number of enteric bacteria such as E. coli. This organism was considered as a good bioindicator model for surveillance studies of antimicrobial resistance. So, only antibiotic resistance pattern of E. coli was determined. A total of 10 E. coli isolates were used for the sensitivity test. All the isolates were totally resistant to Rifampin and Bacitracin (100%). Most of the isolates were found highly resistant to Tetracycline (90%) and Erythromycin (90%), moderately resistant to Amoxicillin (70%), Streptomycin (70%) and Novobiocin (60%). On the other hand, the isolates were totally sensitive to Gentamycin (100%) and Kanamycin (90%) and highly sensitive to Chloramphenicol (80%). Key words: Municipal tap water, Bacteriological safety assessment, Quality, Bottle water, Health hazard DOI: http://dx.doi.org/10.3329/bjmm.v4i1.8462 BJMM 2011; 4(1): 9-13